Exploring neoliberalism in care for people with intellectual disabilities: A practice theory approach. Issue 2 (3rd April 2019) - Gappmayer, Georg
ABSTRACT: Introduction: Occupational scientists and social scientists observe a continuing ascendancy of neoliberal ideals in care. This study investigated how these ideals influence group homes for adults with intellectual disabilities (ID) in Austria. Method: Data were collected in ethnographic fieldwork between 2011 and 2015, comprising participant observation and formal and informal interviews with caregivers, residents, and one executive in three supervised group homes, plus review of organizational policy documents. Data analysis was informed by a grounded theory approach and situational analysis. Schatzki's practice theory was used to capture the influence of society and social values on individuals' occupations. Findings: Analysis revealed that the policy documents of organizations for people with ID were informed by neoliberal values in care. This became visible through the omnipresence of the idealization of being independent and self-determined. While these aims guided some occupations in the group homes, the aim of providing/consuming guided most of the occupations. This aim was absent in the policy documents. Discussion: The mismatch between policy documents and practices that were lived out were the result of the skill level of the residents and the caregivers' obligation to maintain the routine of the group homes. The focus on self-determination and independence is an attempt to enhance the personhood status of people with ID, but does not always lead to good care. Residents fail to reach this normative objective, creating tension between neoliberal values and dependency in care in which all actors are stuck.